Single layer dual wideband linear to circular polarisation converter with integrated parasitic elements - Nkimbeng, Cho Hilary Scott; Wang, Heesu; Yoon, Daeyeong; Park, Yong Bae; Park, Ikmo (Scientific Reports, 2024)
This paper presents a novel single-layer, single-sided, dual-wideband linear-to-circular (LTC) polarsation converter. The unit cell of the polarisation converter comprises two identical diagonally oriented C-shaped metallic strips arranged symmetrically and integrated with four outwardly extending diagonal parasitic strips. The LTC polarisation converter is placed on the top side of an ultra-thin substrate layer with a profile size of 0.020 λo at 11.9 GHz and 0.05 λo at 30.7 GHz. The inclusion of parasitic strips in the unit cell design is pivotal, inducing a 90º phase shift between the orthogonal wave components, thus enhancing LTC polarisation conversion. The design achieved near-equal transmission amplitudes and maintained a stable phase difference of nearly 90° across two distinct frequency bands, enabling right-hand circular polarisation in the lower frequency band and left-hand circular polarisation in the higher frequency band. Numerical and experimental results showed that the polariser can realise a wideband LTC polarisation conversion for both x- and y-polarised electromagnetic wave incidences at two distinct frequency bands of 6.78–17.08 GHz (fractional bandwidth of 86.3%) and 25.09–36.40 GHz (36.8%). The converter maintained consistent polarisation conversion performance across a broad range of incidence angles and exhibited high and uniform total transmittance in both operational frequency bands.
Keywords: Circular polarisation; Linear polarisation; Linear-to-circular polarisation converter; Transmission coefficient; Ultra-wideband